Crotoxin: Novel activities for a classic beta-neurotoxin - Sampaio, Sandra C.; Hyslop, Stephen; Fontes, Marcos R. M. [UNESP]; Prado-Franceschi, Julia; Zambelli, Vanessa O.; Magro, Angelo J. [UNESP]; Brigatte, Patricia; Gutierrez, Vanessa P.; Cury, Yara (Pergamon-Elsevier B.V. Ltd, 2010)
Crotoxin, the main toxin of South American rattlesnake (Crotalus durissus terrificus) venom, was the first snake venom protein to be purified and crystallized. Crotoxin is a heterodimeric beta-neurotoxin that consists of a weakly toxic basic phospholipase A(2) and a nonenzymatic, non-toxic acidic component (crotapotin). The classic biological activities normally attributed to crotoxin include neurotoxicity, myotoxicity, nephrotoxicity and cardiotoxicity. However, numerous studies in recent years have shown that crotoxin also has immunomodulatory, anti-inflammatory, anti-microbial, anti-tumor and analgesic actions. In this review, we describe the historical background to the discovery of crotoxin and its main toxic activities and then discuss recent structure-function studies and investigations that have led to the identification of novel pharmacological activities for the toxin. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Anti-inflammatory; Anti-microbial; Antinociception; Anti-tumor activity; Crotoxin; Immunomodulation; Neurotoxicity